2005
DOI: 10.1021/tx049762o
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Pathway of Hydroquinone Induced Apoptosis Occurs via Both Caspase-Dependent and Caspase-Independent Mechanisms

Abstract: The role of mitochondria and apical caspases in apoptosis induced by the benzene metabolite hydroquinone (HQ) remains to be elucidated. Here, we investigated the involvement of mitochondria and activation of the apical caspases-8 and -9 in HQ induced apoptosis in myeloperoxidase (MPO)-rich HL-60 and MPO-deficient Jurkat T cells. Treatment of HL-60 and Jurkat cells with HQ resulted in apoptosis as assessed by phosphatidyl serine (PS) exposure, loss of mitochondrial transmembrane potential (MTP), release of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Findings from the present study are consistent with previous reports of adverse effects of benzene on oxidative stress (Kolachana et al 1993) and mitochondria (Inayat-Hussain and Ross 2005). Here, we found highly significant associations with ATP synthesis–coupled proton transport and oxidative phosphorylation at all levels of benzene exposure relative to unexposed controls.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Findings from the present study are consistent with previous reports of adverse effects of benzene on oxidative stress (Kolachana et al 1993) and mitochondria (Inayat-Hussain and Ross 2005). Here, we found highly significant associations with ATP synthesis–coupled proton transport and oxidative phosphorylation at all levels of benzene exposure relative to unexposed controls.…”
Section: Discussionsupporting
confidence: 94%
“…HMOX1 [heme oxygenase (decycling) 1], an antioxidant and suppressor of TNF-α signaling (Lee et al 2009), was down-regulated in the low-dose benzene exposure group. Increased mitochondrial membrane permeability potential induced by benzene metabolites (Inayat-Hussain and Ross 2005) can lead to the initiation of apoptosis. Indeed, apoptosis was associated with all benzene doses in the present study, consistent with our earlier observation of an association with high-dose benzene exposure (> 10 ppm) (McHale et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Further study is necessary to elucidate the mechanisms underlying the cytotoxic effect of benzene and the interplay between the molecules involved. In addition, other mechanisms potentially mediating the effect of HQ on BMSCs should be investigated, such as the involvement of caspases, as the induction of cell death by benzene and its metabolites has been shown to be mediated by the modulation of several genes including Bcl-2, Bax, caspases 9, 11 and 12, ELK-member of ETS oncogene family and Fau [41,42], as well as by oxidative DNA damage resulting from the production of reactive oxygen species in response to HQ [43].…”
Section: Discussionmentioning
confidence: 99%
“…While the nature of caspase-independent gingipain-induced apoptosis in BCAEC needs to be further characterized, there are several proteins that maybe involved in this pathway that merit initial studies. For example, AIF was identified in human coronary artery endothelial cells outside the nucleus in the basal state and translocated to the nucleus upon induction of apoptosis in a caspase-independent manner (236) Moreover, treatment of BCAEC with gingipains may affect mitochondrial function (17), leading to the release AIF and/or endoG, both of which induce apoptotic morphology (89). Another possible protein involved in gingipain-induced caspaseindependent signaling pathway could be Bax since it induces cytochrome c release that is not inhibited by z-VAD-FMK (9).…”
Section: Caspase-independent P Gingivalis -Induced Apoptosismentioning
confidence: 99%
“…In cells in which P. gingivalis can induce apoptosis, is this because of direct pro-apoptotic signaling by P. gingivalis or because of a specific survival signal that is absent in those cells and is essential to prevent P. gingivalis-induced apoptosis? For instance, a recent report demonstrated that the same apoptotic stimulus induced an intrinsic apoptosis that was caspase-dependent in one cell type and caspase-independent in a different cell type (89), implying cellular differences and not apoptotic stimulus differences. In cells that survive despite P. gingivalis infection, is this because P. gingivalis is overriding the host cell's apoptotic reflex or because the cell is 'ambivalent' to the presence of the invading bacterium?…”
Section: P Gingivalis-induced Resistance To Apoptosismentioning
confidence: 99%